Cultivating Success: Strategies for Small Pig Farmer Enhancement - Manju bargavi SK, Vikram singh, Sunil Sharma (Revista Electronica de Veterinaria, 2024)
Pig farming by smallholders has been an essential source of income for poor tribal populations in Assam, an important area in India. With the use of interventions in knowledge acquisition, pig variety substitution, shelter management and veterinary services, recent research aimed to increase the ability of these smallholder pig farmers. Using pre-made, semi-structured questionnaires, a two-stage stratified random sample with 180 tribal farmers was carried out before and after the treatments. After implementing enhanced husbandry methods and improving shelter management, 70% of beneficiaries reported satisfactory conditions in and around pig shelters, while 25% indicated perfect conditions. Notably, high-yielding native or exotic crossbred pigs in the region supplanted bland local pig species by 50%. Prior to the interventions, 86.2% of farmers bred pigs for fattening; however, 91.8% of them started breeding sows to produce piglets. These approaches fostered beneficial improvements in agricultural methods by demonstrating a solid influence on raising and socio-psychological aspects. The adoption of a "piglet production farming system" strengthened food security in the area while improving raising circumstances.